Malignant phyllodes tumor of the breast in a young patient –case report - Haddad, Cássio Furtini; Paiva, Ana Carolina de Oliveira; Silva, Juan Pablo de Souza; Rodrigues, Isabela Teixeira (Mastology, 2024)
Phyllodes tumor (PT) is an uncommon form of breast tumor. It occurs most commonly in women aged 35 to 65 years. The benign form represents about 85–90% of cases and only 10–15% of PTs are malignant. Clinically and radiologically, malignant phyllodes tumor (MPT) presents as regular, well-delimited, mobile nodules that are difficult to distinguish from fibroadenomas of the breast. The most important differential diagnoses of MPT include fibroadenoma, metaplastic carcinoma, and sarcoma. The prognosis of MPT exhibits a higher frequency of local recurrence and metastatic rate with larger tumors and inadequate surgical margins. The case presented here refers to a 24-year-old female patient, with a vast tumor in the right breast, with rapid and progressive growth, associated to local pain, and histological diagnosis of MPT. Surgery was the initial treatment, followed by adjuvant chemotherapy and radiotherapy. The purpose of this article was to report an atypical case of MPT of the breast in a very young woman as well as to make a brief literature review on this infrequent and dangerous disease.